Is The ‘Rule of Tens’ a Necessary Screening Criteria in Cleft Lip Surgeries - Ibadurahman, Ibadurahman; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: The “rule of tens” (ROT) is still widely applied nowadays in many cleft centers worldwide for cleft lip surgery, although many surgeons do not implement it as a standard ru Recent advances in the field of anesthesiology have enhanced the safety of surgery for neonates. In Indonesia, ROT is still applied but is still flexible, due to some pertaining social confiicts. The relevance of ROT to the rate of mortality and morbidity is still unknown. This study aims to assess the need of using ROT in cleft lip surgeries.Methods: A retrospective study was conducted. Data was obtained from the medical records of patients who had undergone cleft lip repair between January 2004 to December 2005 in one day care setting. All data related to ROT parameters was categorized in two groups, either fit or unfit according to ROT criterias. The relationship of ROT to rate of associated morbidity and mortality was evaluated.Results: There were 204 cases of cleft lip repair with age range of 6-week to 12-year old. More than half (52.9%) was unfit for ROT. There were twelve cases of wound dehiscence and one total breakdown of the sutures, and no mortality. There were no statistically significant correlation ce between ROT and the rate of dehiscence. Conclusion: ROT is not a definitive criterion that could predict the success of cleft lip repair surgery.